Microbiological, phytochemical constituents, and antioxidant properties of fermented green Robusta coffee beans - Chan, Hao Yuan; Rukayadi, Yaya; Mohamad Azman, Ezzat; Ashaari, Rozzamri; Lim, Sarina Abdul Halim (Universiti Putra Malaysia, 2024)
Robusta coffee is one of Malaysia’s most planted species due to its ability to adapt to the local climate. Nonetheless, the coffee species was perceived as having lower quality and economic value due to bitterness and astringency. It is widely believed that higher caffeine and chlorogenic acid contents in Robusta coffee beans contributed to the unfavourable bitter and astringent flavour. Hence, the present study intends to evaluate the effect of spontaneous wet fermentation (SWF) of locally grown Robusta (Coffea canephora L.) coffee towards the microbiological properties, phytochemical constituents, in particular caffeine and chlorogenic acids (CGA), total phenolic content (TPC), and antioxidant properties. The SWF of green Robusta coffee beans from University Agricultural Park (UAP), Universiti Putra Malaysia, Serdang, Selangor, took place at ambient temperatures between 25 to 28°C, and the pH decreased from 5.2 to 3.64 over five days of fermentation. The total plate count, lactic acid bacteria (LAB) and yeasts were significantly increased to approximately 7 Log10 CFU/g. The SWF has reduced caffeine content by 35%, while the CGA has decreased by roughly 20%. The SWF also led to an increase in TPC of approximately 31.5% and an increase in antioxidant activity of approximately 60%.